Faktor-Faktor yang Mempengaruhi Stunting pada Balita di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2025 - Nurmalina Hutahaean; Siti Nurmawan Sinaga; Ika Damayanti Sipayung; Elvis Simanjuntak; Merrygrace Simanjuntak (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Stunting is a global concern, impacting the quality of human resources.Purpose of Analysis of Factors Related to Stunting in Toddlers in Bangun Rejo Village, Tanjung Morawa. This study used a cross-sectional study design analytical method. The population of this study is 35 stunted toddlers in the February-March 2025 period. 16 respondents with moderate knowledge, the majority of toddlers were stunted with short height (75%), while the other 25% were very short. The results of the statistical test showed a P-Value of 0.000 (P < 0.05), 22 secondary education respondents, most of them toddlers experienced stunting, short height (72.7%), while the other 27.3% were very short. showed a P-Value of 0.003 (P < 0.05), 20 low-income respondents, 60% of toddlers experienced stunting very short height, while 40% were short. showed a P-Value of 0.015 (P < 0.05), indicating a significant relationship between income and stunting in toddlers, 24 respondents had undernourished status, 54.2% of toddlers experienced stunting, very short height, while 45.8% were short. showed a P-Value of 0.006 (P < 0.05), there was a significant relationship between nutritional status and stunting in toddlers. Knowledge, education, income, nutritional status are risk factors for stunting in toddlers.Increasing knowledge of child growth is very important to understand the factors that affect stunting and effective prevention strategies.